Educational Policies on Family–School Relations: A Dimensional Analysis Across Five Nations - Kirmaci, Mehtap (International Journal about Parents in Education, 2023)
Worldwide interest in improving family-school interactions sets the stage for examining how national reform policies have influenced the promotion of family and school partnerships. I examined the history of changing policies concerning home-school relations in five countries: The United States, Australia, Canada, Finland and Sweden. Common themes emerged that reflect two co-existing educational ideologies across the nations—collaboration and consumerism. The contradictory nature of these ideas and the ensuing confusion can weaken the implementation of family-school collaborations. Researchers in the United States, Canada, Australia, and Sweden have already raised concerns about the weak effects of partnership policies on parent-school relations for families of diverse ethnic and linguistic backgrounds. In addition to promoting family-school collaborations, policy makers should consider developing resources and strategies for facilitating partnerships.